Botrytis cinerea elicitation enhances glucose transport in Pinus pinaster suspension cultured cells - Azevedo, Herlânder (2004)
Pinus pinaster Ait.(maritime pine) is a two-needle pine widely distributed throughout the west Mediterranean basin. It is a pioneer and economically important forest species, being considered one of the most important pines in Europe. The Ascomycota Botrytis cinerea is the necrotrophic fungus responsible for the grey mould disease infecting over two hundred different hosts. Adult populations of maritime pine are resistant to B. cinerea infection, but seedling nurseries and young plantations are often infected. Plant-microbe interactions involve an array of complex changes in plant cell metabolism. In most incompatible interactions the Hypersensitive Response by plant cells culminates in programmed cell death, preventing progress of the pathogen. Cell suspensions of P. pinaster were able to transport glucose by a monosaccharide/H+ symporter with the following kinetic parameters: Km = 0.05 mM glucose and Vmax = 1.5 nmol min-1 mg-1 DW. The carrier accepted D-glucose, D-fructose, D-galactose, D-xylose, 2-deoxy-D-glucose, and 3-O-methyl-D-glucose, but not L-glucose, sucrose and D-mannitol. High sugar concentrations repressed carrier activity. The elicitation of glucose partially repressed P. pinaster cultured cells with a spore suspension of B. cinerea promoted a 4-fold increase of Vmax. Enhanced glucose uptake depended on the activation of some defence signal transduction pathway components such as NADPH oxidase and calcium influx but not MAPKinases. De novo protein synthesis appears to be required because 50 µg ml-1 cycloheximide maintained carrier capacity at basal levels.